The Challenges of On-site Waste Management Innovation in Building Construction Projects: Lebanese Construction Industry - Merhi, Riad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Construction and demolition (C&D) waste generation is considered to be one of the real problems in the construction industry (CI) today. This is because of its direct negative impacts on the efficiency of the CI in addition to the environment. Because the CI is depending on environmental resources, it can’t keep on practicing if these sources are being depleted, therefore the significance of waste management innovation on-site such as separation, processing and re-use of C&D waste is vital to bring forth significant social, economic and environmental benefits over traditional methods. The CI takes an important part in the economy of developing countries, such as Lebanon. The aim of this thesis is to investigate the behavioral determinants effecting on-site C&D waste management innovation (OC&DWMI) decisions. For this purpose, a questionnaire survey was distributed between different contractors within the Lebanese CI. A preliminary theoretical model that integrates two key behavioral decision-making theories was developed based on the theory of planned behavior and innovation diffusion theory with additional significant constructs. Structural Equation Modelling was used for data analysis, model modification, and hypothesis testing. A conceptual framework was developed showing the most significant factors. Whereas the results of the final model show that behavioral intention concerning OC&DWMI and governmental supervision are the most significant factors affecting the adoption decisions of OC&DWMI. So governments should impose specific regulations and guidelines regarding OC&DWMI with comprehensive supervision and strict punishment system, in addition to the help of R&D institutions and professional associations in increasing the behavioral intention regarding OC&DWMI to achieve its adoption.

ÖZ: İnşaat ve yıkımdaki (İY) atık üretiminin günümüz inşaat sektörünün (İS) gerçekl sorunlardan biri olduğu düşünülmektedir. Bunun nedeni çevreye ilaveten İS'nün etkinliği üzerinde doğrudan olumsuz etkileri olmasıdır. İS, çevresel kaynaklara bağlı olduğu için, bu kaynaklar tükenirse uygulamaya devam edilemez, bu nedenle, İY’daki atıkların ayrılması, işlenmesi ve tekrar kullanımı gibi sahadaki atık yönetimi inovasyonunun önemi, geleneksel yöntemlere kıyasla önemli sosyal, ekonomik ve çevresel yararlar sağlamak için hayati öneme sahiptir. İS, Lübnan gibi gelişmekte olan ülkelerin ekonomisinde önemli bir yere sahiptir. Bu tezin amacı, sahadaki İY atık yönetimi inovasyonu (SİYAYİ) kararlarını etkileyen davranışsal etkenlerin araştırılmasıdır. Bu amaçla, Lübnan İS’ndeki farklı yükleniciler arasında bir anket formu dağıtıldı. İki önemli davranışsal karar verme kuramını bütünleştiren ön teorik model, planlanmış davranış teorisi ve inovasyon yayılım teorisine dayanılarak ilave önemli düzenlerle geliştirilmiştir. Yapısal Eşitlik Modellemesi, veri analizi, model modifikasyonu ve hipotez testi için kullanılmıştır. En önemli faktörleri gösteren bir kavramsal çerçeve geliştirilmiştir. Son modelin sonuçları, SİYAYİ ve hükümet denetimine ilişkin davranışsal niyetin SİYAYİ 'nin benimsenmesiyle ilgili kararlarını etkileyen en önemli faktörler olduğunu göstermektedir. Bu nedenle, hükümetler, SİYAYİ 'nin benimsenmesini sağlamak için davranış niyetini artırmada Ar-Ge kurumları ve meslek kuruluşlarının yardımına ek olarak, kapsamlı kontrol ve sıkı ceza sistemi ile SİYAYİ ile ilgili özel düzenlemeler ve yönergeler koymalıdır.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2017. Supervisor: Assoc. Prof. Dr. İbrahim Yitmen.
Keywords: Civil Engineering; Waste management--Building construction; Construction and Recycling; Construction industry--Environmental aspects; Construction and demolition waste management; Intention; Theory of planned behavior; Behavioral determinant